Physical, structural, and optical properties of zinc silicate-based glass-ceramic derived from zinc boro soda lime silica glass system - Mohd Shofri, Muhammad Faris Syazwan (2021)
Zinc silicate or willemite (Zn2SiO4) is a crystal that have unique optical characteristic which make it as a potential material in optoelectronic applications. It is also suitable for application in coating, catalyst, cathode ray tube (CRT), plasma display panels (PDPs), laser, and electroluminescent devices. In this study, a ZnO‒SLS‒B2O3 glass system have been fabricate using conventional melt-quench method and followed by an isothermal heat treatment process to synthesize zinc silicate based glass-ceramics. This project using empirical formula of (ZnO)60-x(SLS)40(B2O3)x where x = 5, 10 and 15 wt.% and heat treated at different temperature from 600 °C to 900 °C with three different holding time of 2, 4, and 10 hours. The physical, structural and optical properties were measured by using average density measurement, linear shrinkage, X-Ray diffraction (XRD), Fourier transform infrared reflection (FTIR), ultraviolet-visible spectroscopy (UV-Vis), energy band gap calculation and photoluminescence spectroscopy (PL). The density of precursor glass measurement show an increased trend from 2.726 to 2.754 g/cm3 as ZnO content increase. The density and linear shrinkage of glass-ceramic show increased trend as progress of heat treatment temperature and duration. The XRD results show the zinc silicate crystal begins to grow after the glass sample being treated at 700 °C for 2 hours. XRD data also observed that the crystallinity of glass-ceramic increased as heat treatment increase. Besides, the FTIR spectra indicated the crystallization of zinc silicate phase occurred with the appearance of SiO4 and ZnO tetrahedral which indicate the formation of zinc silicate crystal with the progress in heat treatment temperature and duration. In addition, UV-visible revealed slight variations where the energy of the optical band gap of precursor glass decreased from 4.40 to 4.00 eV due to the increase in ZnO content. The optical band gap of glass-ceramic also decrease with the progress in heat treatment temperature and duration. The PL spectroscopy also revealed an improvement in broad green emission at 550 nm after excite at 360nm wavelength due to the development of zinc silicate crystal in the glass-ceramic samples. From the results, with such optical properties of the zinc silicate glass-ceramic is expected to find potential application in phosphors and opto-electronic devices.